Effects of Quality Control Targets (SpO2≠100%, PaCO2/<40 mmHg, Pmean/>10 cmH2O) on Outcomes in Patients in the ICU - Pan, Pan; Su, Longxiang; Zhang, Qing; Long, Yun; Wang, Xiaoting; Liu, Dawei (Frontiers in Medicine, 2020)
Objectives: A series of quality control (QC) targets (SpO2≠100%, PaCO2≮40 mmHg, Pmean≯10 cmH2O) was put forward and widely used in a single intensive care unit (ICU) setting.The aim of this study was to assess whether these QC targets could improve the outcomes of critically ill patients. Methods: The real-time clinical data of patients undergoingmechanical ventilation at ICU admission between May 2013 and May 2017 in the Department of Critical Care Medicine of Peking Union Medical College Hospital were collected and analyzed. Results: A total of 7,670 patients (mean age, 58 years; 3,943 [51.5%] male) were divided into the before QC (n = 3,936) andafter QC (n = 3,734) groups. QC targets (SpO2, PaCO2, Pmean) and respiratory parameters (FiO2%, PaO2, PEEP, tidal volume, respiratory rate) within 72hours of ICU admission, primary outcomes (ICU mortality, 28-day, 60-day, and 90-day mortality) and secondary outcomes (dischargeagainst medical advice, ICU admission days, mechanical ventilation times, and central venous pressure) were measured, and compared between the before and after QC groups. The72-hour average of thePmean, FiO2%, PaO2, and VT were significantly lower and PaCO2 was higher in the after QC than in the before QC group (P<0.05). A lower 90-day mortality rate, less dischargeagainst medical advice, fewer ICU admission days and reduced mechanical ventilation times were found in the after QC group compared with the before QC group (P<0.05). Interestingly, CVP was significantly lowerin the after QC group than in the before QC group (P<0.05). Conclusions:The QC targets(SpO2≠100%, PaCO2≮40 mmHg, Pmean≯10 cmH2O) contributed to avoiding high oxygen level hazards, protectingagainst lung injury, and improving circulatory function, which resulted in a better prognosis of critically ill patients.